Both non-type species of Molytophilus (Coleoptera: Curculionidae: Molytinae) are transferred to Oreoscotus - Grebennikov, Vasily V. (Zootaxa, 2018)
Type specimens of all three nominal species of the East African genus Molytophilus Hartmann are studied and illustrated. The genus is taxonomically restricted to include only the type species M. carinatus Hartman known from two collecting events in Tanzania and Somalia. Both other species of Molytophilus, described from Ethiopia, are herein transferred to the genus Oreoscotus as O. affinis (Hustache, 1936) comb. n. and O. puncticollis (Hustache, 1936) comb. n. A lectotype is designated for Molytophilus carinatus Hartmann. Type specimens of all three nominal species are illustrated.